Providing the right dose instructions. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
The General Medical Council -funded PRACtICe study investigated the prevalence and causes of prescribing errors in general practices. The results showed that around one in three of the prescribing errors detected were associated with incomplete information on the prescription whilst around one in 10 involved giving a medicine at the wrong time. In this article we focus on achieving clear and unambiguous dosing instructions including how clinical computer systems can help to alleviate the problem. We also look at the cautionary and advisory labels added during the dispensing process. The article gives the reader opportunities to reflect upon different scenarios, and there are also suggestions for additional continuing professional development activities.